Mental health in Ireland during the covid pandemic: Evidence from two longitudinal surveys - David Madden (University College Dublin, UCD School of Economics, 2022)
Using data from the Growing Up in Ireland Covid survey, this study examines the evolution of mental health as measured in December 2020, nine months into the pandemic, compared to observations pre pandemic for two cohorts of people. A deterioration in mental health was observed for both cohorts and particularly for younger women of the 1998 cohort. The increase in the rate of depression predominantly occurred due to an overall decline in mental health rather than being concentrated amongst those already vulnerable (in the sense of being near the depression threshold). There was little, if any, change in the socioeconomic gradient associated with mental health and virtually no gradient at all was observed pre or post pandemic for the 1998 cohort. Mobility analysis revealed that not only did females from the 1998 cohort show greater transitions into depression, they also appeared to transition into more extreme levels of depression.
Keywords: I14; I31; 330; Mental health; depression; Shapley decomposition; concentration index